Administration of phospholipide hepatoprotective drug Phosphogliv in patients with psoriatic arthritis (preliminary results) - T. V. Korotaeva; E. L. Nassonov; O. M. Ipatova; N N Firsov; O A Fvkina; TA Torhovskaya; A. I. Archakov (Научно-практическая ревматология, 2004)
Considering membrane-reparative properties of a new phospholipid hepatoprotector Phosphogliv (FG) its therapeutic efficacy was assessed in 9 pts with psoriatic arthritis (PA) accompanied by prominent disturbances of blood rheology. FG was given 0,6 g a day during 3 months. Significant decrease of erythrocyte aggregation resulting in increase of erythrocyte aggregation formation time and diminishment of their hydrodynamic resistance without changes of whole blood general caisson viscosity was achieved. Significant improvement of Richie index, tender joint count and pt assessment was noted. The results prove availability of PG administration in PA therapy and possibility of enlargement PG application area owing to membrane-reparative properties of contained in it polyunsaturated phosphatidilcholin in combination with immunomodulating and anti-inflammatory action of glycyrrhizinic acid.